2017
DOI: 10.1016/j.celrep.2017.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Modifications of OLIG2 Regulate Glioma Invasion through the TGF-β Pathway

Abstract: contributed RNA samples from pre-hypertrophic mouse models and assisted with computational analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Notably, we and others showed that a large population of OLIG2 + cells in human gliomas, particularly proneural GBMs, expresses the proliferative marker Ki67 and the stem-cell marker CD133, suggesting that proliferative OLIG2 + cells are tumor-propagating cells (Ligon et al, 2007;F. Lu et al, 2016;S. K. Singh et al, 2016).…”
Section: Oligodendrocyte Precursor Cellsmentioning
confidence: 73%
See 1 more Smart Citation
“…Notably, we and others showed that a large population of OLIG2 + cells in human gliomas, particularly proneural GBMs, expresses the proliferative marker Ki67 and the stem-cell marker CD133, suggesting that proliferative OLIG2 + cells are tumor-propagating cells (Ligon et al, 2007;F. Lu et al, 2016;S. K. Singh et al, 2016).…”
Section: Oligodendrocyte Precursor Cellsmentioning
confidence: 73%
“…Interestingly, OLIG2 appears to be ubiquitously expressed in human gliomas (Ligon et al, 2004; Q. R. Lu et al, 2001) and has a regulatory role in glioma initiation and tumor phenotype plasticity (Kupp et al, 2016;Ligon et al, 2007;F. Lu et al, 2016;S. K. Singh et al, 2016).…”
Section: Core Transcriptional Regulators Of Neurodevelopment and Tumorigenesis Crosstalkmentioning
confidence: 99%
“…Phosphorylation of this motif is developmentally regulated and it is the phosphorylated form of Olig2 that has gliomagenic and anti-p53 functions (Sun et al, 2011). A more recent study demonstrates that this phosphorylation also regulates the switch from the proliferation to invasion in glioma cells (Singh et al, 2016). In studies summarized here, we use mass spectrometry, genetics and test tube biochemistry with synthetic peptides to identify a set of three protein kinases that are collectively both necessary and sufficient to phosphorylate the triple serine motif.…”
Section: Introductionmentioning
confidence: 99%